Management of Neglected Floating Knee with Rotational Deformity and Limb Shortening Using the Ortho-SUV Frame: A Case Report - Vishal S Patil; Mohammed Talha Muneer; Archit Gupta; Raj Kamble (Journal of Clinical and Diagnostic Research)
Floating Knee Injury (FKI) are associated with significant complications, including deformity and limb shortening. The Ortho-Solomin-Utekhin-Vilensky (SUV) (OSF) system, integrated with computer software for precision correction, offers an effective solution for treating complex cases, particularly those with rotational deformities. Hereby the authors present the case of a 38-year-old male who sustained a floating knee injury following a high-velocity Road Traffic Accident (RTA). Initial management included stabilisation with an external fixator following Damage Control Orthopaedic (DCO) principles. However, the patient was lost to follow-up and presented three months later with a neglected flexion deformity and significant external rotation of the knee. Clinical and radiological findings showed malunion, knee deformity and a limb length discrepancy of 2 cm. The external fixator was removed and deformity correction and limb lengthening were planned using the OSF frame, a hexapod system designed for complex deformity corrections. Intraoperative findings revealed full-thickness quadriceps muscle loss. The OSF system was used to correct rotational deformities and induce limb lengthening through corticotomy and distraction osteogenesis over a three-month period. Radiological assessments confirmed new bone formation, although residual proximal tibia displacement required screw fixation. After six weeks of non weight bearing, the patient achieved full weight-bearing with normal range of motion. The present case highlights the utility of the OSF system in achieving deformity correction and limb lengthening, demonstrating satisfactory functional outcomes in a neglected floating knee injury. The case underscores the importance of timely follow-up and the role of advanced external fixation techniques in managing complicated orthopaedic injuries.